A Comprehensive Overview of Diabetic Pneumopathy - Asim Minhas (KARACHI MEDICAL AND DENTAL COLLEGE, 2024)
Diabetes mellitus (DM) is characterized by hyperglycemia, a chronic metabolic condition brought on by deficits in either insulin action or secretion, or both. While the primary objectives of diabetes treatment are often glycaemic control and prevention of sequelae such as neuropathy, nephropathy, and retinopathy, an increasing amount of evidence points to a complex relationship between diabetes and lung issues. Among these, diabetic pneumopathy is one that is gaining more recognition. It is distinguished by anomalies in the lung's anatomy and function. The purpose of this review is to provide a comprehensive understanding of diabetic pneumopathy by investigating its pathogenesis, clinical symptoms, diagnosis, and therapeutic methods.